Cost of Equity Analysis through the role of Earnings Aggressiveness and Profit Persistence: Evidence from Manufacturing Companies in Indonesia - Atang Hermawan; Dewi Ayu Anggita Sari; Ardi Gunardi (International Business and Accounting Research Journal, 2021)
To survive, companies need to make various business development efforts which require capital that not all companies can fulfill independently. So in this case the company needs other parties (external parties) to meet its capital needs, namely investors and creditors. Obtaining capital from external parties, be it share capital or loans, poses their respective risks. Therefore, this study aims to provide an overview of how earnings aggressiveness, earnings persistence, and cost of equity are in manufacturing companies listed on the Indonesia Stock Exchange for the 2014-2018 period. Earnings persistence as moderating variables considering that these variables can be indicators of future earnings obtained in the long term. The research method used is descriptive verification method with data analysis is done by Simple Linear Regression Analysis, Moderated Regression Analysis (MRA), classical assumption test, correlation analysis, and coefficient of determination. While the hypothesis testing used is a statistical method of partial test (t test) using SPSS 20 for Windows. The results of this study indicate that earnings aggressiveness has a positive effect on the cost of equity and the persistence of earnings as a moderating variable weakens the effect of earnings aggressiveness on the cost of equity